PENINGKATAN KEMAMPUAN MEMBUAT MIE TITI MELALUI METODE PEMBELAJARAN LANGSUNG PADA SISWA TUNARUNGU KELAS XI DI SLB YPAC MAKASSAR - Sahir, Irmaya; Meidina, Tatiana; Mustafa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The problem in this study is the low ability to make titi noodles in deaf students of grade XI at SLB YPAC Makassar, which is caused by the less than optimal use of learning methods that are appropriate to the characteristics of the students. The purpose of this study is to: (1) determine the ability to make titi noodles in deaf students of grade XI at SLB YPAC Makassar before the implementation of direct learning methods, (2) determine the ability to make titi noodles after the implementation of direct learning methods, and (3) determine the increase in the ability to make titi noodles through the implementation of direct learning methods at SLB YPAC Makassar. This study uses a quantitative approach with a descriptive research type. The data collection technique is carried out through observation tests. The data obtained are analyzed descriptively quantitatively to describe the students' abilities before and after the implementation of direct learning methods in the skill of making titi noodles. The results of the study show that the ability to make titi noodles in deaf students of grade XI at SLB YPAC Makassar has increased after the implementation of direct learning methods. Students' abilities before treatment are still relatively low, but after the implementation of direct learning methods show a significant increase. Thus, it can be concluded that the direct learning method is effective in improving the ability to make Titi noodles in eleventh-grade deaf students at the YPAC Special Needs School in Makassar.